2017
DOI: 10.18632/oncotarget.16824
|View full text |Cite
|
Sign up to set email alerts
|

Identification of common immunodominant antigens of Eimeria tenella, Eimeria acervulina and Eimeria maxima by immunoproteomic analysis

Abstract: Clinical chicken coccidiosis is mostly caused by simultaneous infection of several Eimeria species, and host immunity against Eimeria is species-specific. It is urgent to identify common immunodominant antigen of Eimeria for developing multivalent anticoccidial vaccines. In this study, sporozoite proteins of Eimeria tenella, Eimeria acervulina and Eimeria maxima were analyzed by two-dimensional electrophoresis (2DE). Western bot analysis was performed on the yielded 2DE gel using antisera of E. tenella E. acer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 68 publications
1
45
2
Order By: Relevance
“…The present study represents the first to show E. acervulina antigens recognized by sera specific to E. acervulina as well as those specific to E. tenella or E. necatrix. Interestingly, most of the E. acervulina proteins with shared immunogenicity identified in the present study were not found in a similar study where anti-E. acervulina sera were used to detect E. acervulina antigens [30]. One apparent difference between the studies is that we used antisera with much higher titers (1:1280), which could in part account for why the proteins identified in our study are not shown in the study by Liu et al [30].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The present study represents the first to show E. acervulina antigens recognized by sera specific to E. acervulina as well as those specific to E. tenella or E. necatrix. Interestingly, most of the E. acervulina proteins with shared immunogenicity identified in the present study were not found in a similar study where anti-E. acervulina sera were used to detect E. acervulina antigens [30]. One apparent difference between the studies is that we used antisera with much higher titers (1:1280), which could in part account for why the proteins identified in our study are not shown in the study by Liu et al [30].…”
Section: Discussioncontrasting
confidence: 74%
“…Interestingly, most of the E. acervulina proteins with shared immunogenicity identified in the present study were not found in a similar study where anti-E. acervulina sera were used to detect E. acervulina antigens [30]. One apparent difference between the studies is that we used antisera with much higher titers (1:1280), which could in part account for why the proteins identified in our study are not shown in the study by Liu et al [30]. Future research is warranted to compare Eimeria antigens identified under similar experimental conditions.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Coccidiosis, a deadly disease of chickens worldwide, seriously hampers birds' productivity and welfare [85]. However, most previous studies mainly focused on revealing the functions of protein molecules or protein-coding genes during Eimeria infection [86][87][88][89]. In the present study, we first identified 818 lncRNAs and 4153 circRNAs in mid-segments of chicken small intestines at 108 h pi of E. necatrix, and found that 95 lncRNAs and 13 circRNAs were significantly differentially regulated due to infection.…”
Section: Discussionmentioning
confidence: 63%
“…However, the reported common antigens were not well identified by sequencing and their protective efficacies have not been evaluated. In the earlier study of our lab, Ea14–3-3 antigen was identified as one of the common immunodominant antigens from E. tenella , E. acervulina and E. maxima [ 14 ]. It has been documented that 14–3-3 proteins are involved in many patho-physiological and cellular immune processes by triggering or interfering with the activity of specific protein associates [ 15 ].…”
Section: Introductionmentioning
confidence: 99%